The Effect of Planting Media and Types of NPK Fertilizers (Compound and Mixed) on the Growth of Oil Palm Seedlings in Pre-Nursery - Firmansyah, Ivan Dwi; Rochmiyati, Sri Manu; Ardiani, Fani (Journal of Agriculture, 2024)
This study aims to determine the effect of planting media composition and types of NPK fertilizers (compound and mixed) on the growth of pre-nursery oil palm seedlings. The study was conducted in September - November 2023 at the Instiper Yogyakarta Education and Research Garden. This study used a factorial experimental method arranged in a completely randomized design (CRD) consisting of two factors, namely the composition of the planting media (clay, sand, sand + clay + organic fertilizer, sand + clay, clay + organic fertilizer, sand + organic fertilizer) and types of NPK compound fertilizers (compound fertilizer 15-15-15 and mixed fertilizer 0.30g Urea + 0.30g TSP + 0.25 g MOP). The results showed that the treatment of NPK fertilizer types (compound and mixed) and planting media composition interacted significantly with the height of pre-nursery oil palm seedlings, where the combination of clay soil media with mixed fertilizers produced a plant height of 25.90 cm. The treatment of planting media composition significantly affects the number of leaves, where the composition of sand + clay + organic fertilizer produces the highest number of leaves, which is 4 strands. Furthermore, treating NPK fertilizer types (compound and mixed) also significantly affects the diameter of pre-nursery oil palm seedlings, where using mixed fertilizers gives the highest stem diameter results, which is 9.46 cm.